Coast‐wide evidence of low pH amelioration by seagrass ecosystems. (31st March 2021) - Ricart, Aurora M.; Ward, Melissa; Hill, Tessa M.; Sanford, Eric; Kroeker, Kristy J.; Takeshita, Yuichiro; Merolla, Sarah; Shukla, Priya; Ninokawa, Aaron T.; Elsmore, Kristen; Gaylord, Brian
Abstract: Global‐scale ocean acidification has spurred interest in the capacity of seagrass ecosystems to increase seawater pH within crucial shoreline habitats through photosynthetic activity. However, the dynamic variability of the coastal carbonate system has impeded generalization into whether seagrass aerobic metabolism ameliorates low pH on physiologically and ecologically relevant timescales. Here we present results of the most extensive study to date of pH modulation by seagrasses, spanning seven meadows ( Zostera marina ) and 1000 km of U.S. west coast over 6 years. Amelioration by seagrass ecosystems compared to non‐vegetated areas occurred 65% of the time (mean increase 0.07 ± 0.008 SE). Events of continuous elevation in pH within seagrass ecosystems, indicating amelioration of low pH, were longer and of greater magnitude than opposing cases of reduced pH or exacerbation. Sustained elevations in pH of >0.1, comparable to a 30% decrease in [H + ], were not restricted only to daylight hours but instead persisted for up to 21 days. Maximal pH elevations occurred in spring and summer during the seagrass growth season, with a tendency for stronger effects in higher latitude meadows. These results indicate that seagrass meadows can locally alleviate low pH conditions for extended periods of time with important implications for the conservation and management of coastal ecosystems. Abstract : The most extensive study to date of pH modulation by seagrasses, spanning seven meadows ( Zostera marina ) and 1000 km of U.S. west coast over 6 years. Amelioration of low pH by seagrass ecosystems occurred most of the time, where events of continuous elevation in pH were longer and of greater magnitude than opposing cases of reduced pH or exacerbation. Sustained elevations in pH were not restricted only to daylight hours. Maximal pH elevations occurred in spring and summer during the seagrass growth season, with a tendency for stronger effects in higher latitude meadows.